Системы управления электроприводом: учебное пособие - Однокопылов И. Г. Иван Георгиевич; Ляпушкин С. В. Сергей Викторович; Воронина Н. А. Наталья Алексеевна; Семенов С. М. Сергей Михайлович (Томск, Изд-во ТПУ, 2025)
Заглавие с титульного экрана